INOVASI FINANCIAL TECHNOLOGY TERHADAP PENINGKATAN INKLUSI KEUANGAN - Dian Ratnasari Yahya; Rika Rahayu (STIE Mahardhika, 2020)
People’s lifestyle in the digital era is very varied, almost all stratum of society use technology to gain information, data, loans, transactions, and others practically and quickly. This study aims to find customer trust on intention to adopt fintect performance, find the effect of fintect promotion on the intention to adopt fintect, find the effect of intention to adopt fintect on financial inclusion. This study used survey methods through questionnaires for respondents who used fintect products (OVO applications) in Surabaya with a total sample of 265 respondents. To find out the responses of the respondents toward fintect products, it uses a Likert scale. The data processing performed by using Partial Least Square (PLS). The results show that there was an influence between customer trust on intention to adopt fintect, there was an influence between fintect promotion on intention to adopt fintect, and there was an influence between intention to adopt fintect on financial inclusion.